An active compression sleeve with variable pressure levels using a wire-fabric mechanism and a soft sensor. (1st October 2019) - Yang, Seung Tae; Ryu, Jae Wook; Park, Se-Hun; Lee, Young Bin; Koo, Sumin Helen; Park, Yong-Lae; Lee, Giuk
Abstract: Compression garments are frequently used in daily life activities as well as in specialized fields, such as medical and sports sciences, to enhance bodily functions. However, conventional compression garments provide a fixed compression force to the body and can thus cause several side effects including discomfort, skin irritation, and loss of circulation when worn incorrectly. Development of a new type of compression garment that can control the compression force is required. This paper proposes a new sleeve-type compression garment that alters its compression force by employing a wire-fabric based mechanism. The proposed sleeve has several benefits compared with conventional methods. It not only is lightweight compared with those with pneumatic actuation but also can generate variable compression force by bidirectional driving of the tendons, which is not possible with other wire driving mechanism, such as shape memory alloy actuation. The proposed garment was manufactured by integrating two-layered fabrics with a soft pressure sensor, a wire actuation system, and a feedback controller. The performance was evaluated using three different experiments that tested the ability of varying and maintaining the compression force. This design can be employed in the field of compression garments and assistive devices to provide a means of applying an accurate and customized compression force to the body.